Modified aluminosilicates display antibacterial activity against nontuberculous mycobacteria and adsorb mycolactone and Mycobacterium ulcerans in vitro - Dermody, Roslyn; Ali, Farizah; Popovich, John; Chen, Shaojiang; Seo, Dong-Kyun; Haydel, Shelley E. (Frontiers in Tropical Diseases, 2022)
Mycobacterium ulcerans (MU) infection of skin and soft tissue leads to chronic skin ulceration known as Buruli ulcer. MU releases a lipid-like toxin, mycolactone, that diffuses into the tissue, effecting disease through localized tissue necrosis and immunosuppression. Cutaneous Buruli ulcer wounds slowly advance from a painless pre-ulcerative stage to an ulcerative lesion, leading to disparities in the timing of medical intervention and treatment outcomes. Novel Buruli ulcer wound management solutions could complement and supplement systemically administered antimicrobials and reduce time to healing. Capitalizing on nanopore structure, adsorption, and exchange capacities, aluminosilicate nanozeolites (nZeos) and geopolymers (GPs) were developed and investigated in the context of therapeutics for mycobacterial disease ulcerative wound care. nZeos were ion exchanged with copper or silver to assess the antimicrobial activity against MU and Mycobacterium marinum, a rapid growing, genetic ancestor of MU that also causes skin and soft tissue infections. Silver- and copper-exchanged nZeos were bactericidal against MU, while only silver-exchanged nZeos killed M. marinum. To mediate adsorption at a biological scale, GPs with different pore sizes and altered surface modifications were generated and assessed for the ability to adsorb MU and mycolactone. Macroporous GPs with and without stearic acid modification equivalently adsorbed MU cells, while mesoporous GPs with stearic acid adsorbed mycolactone toxin significantly better than mesoporous GPs or GPs modified with phenyltriethoxysilane (PTES). In cytotoxicity assays, Cu-nZeos lacked toxicity against Detroit 551, U-937, and WM-115 cells. GPs demonstrated limited cytotoxicity in Detroit 551 and WM-115, but produced time-dependent toxicity in U-937 cells. With their large surface area and adsorptive capacities, aluminosilicates nZeos and GPs may be modified and developed to support conventional BU wound care. Topical application of nZeos and GPs could kill MU within the cutaneous wound environment and physically remove MU and mycolactone with wound dressing changes, thereby improving wound healing and overall patient outcomes.